백내장수술 후 발생한 비전형적 임상양상의 스트렙토코커스 디스갈락티아 안내염 2예 - 유웅선(Woong-Sun Yoo), 강현지(Hyun-Ji Kang), 정지성(Ji-Sung Jeong), 신민호(Ji-Sung Jeong), 정인영(Inyoung Chung) (Daihan angwa haghoi jabji, 2019)
목적: 백내장수술 후 Streptococcus dysgalactiae subspecies equisimilis (SDSE)에 의한 안내염으로 초급성 발현과 전안구염의 비전형적 증상을 보인 2예를 보고하고자 한다. 증례요약: 68세 환자가 백내장수술 후 24시간 이내에 발생한 시력저하로 내원하였으며, 시력은 광각 상태였으며 안구 내 심한 염증 소견으로 유리체절제술과 유리체내 항생제 주사를 시행하였다. SDSE가 동정되었으며 수술 후 염증은 호전되었으나 각막부종은 지속되었고 술 후 3개월째 수포각막병증과 안구위축으로 진행하였다. 87세 환자가 2일 전 백내장수술 후 시력저하와 안구통증으로 내원하였다. 내원 시 시력은 광각무 상태로 안구 내 심한 염증 소견과 각막궤사로 유리체내 항생제 주사만 시행하였다. SDSE가 동정되었고 술 후 4일째 전안구염 소견이 관찰되어 항생제 정맥주사 후 호전되었으나 술 후 3개월째 안구위축으로 진행하였다. 결론: 수술 후 발생한 SDSE 안내염은 초급성의 양상을 보이며 즉각적인 치료에도 호전되지 않아 실명으로 진행되기도 한다. SDSE는 최근 발견이 증가되는 추세로 수술 후 발생한 안내염에서 원인균으로 반드시 고려해야 할 것이다. Purpose: To report two cases of postoperative endophthalmitis caused by Streptococcus dysgalactiae subspecies equisimilis (SDSE), which appeared as hyperacute presentation and panophthalmitis. Case summary: A 68-year-old male was treated with cataract surgery and was evaluated the next day (less than 24 hours after surgery) because of acute loss of vision. There was severe inflammation and the visual acuity was light perception. The patient underwent pars plana vitrectomy (PPV) with intravitreal antibiotic injection. The vitreous culture revealed SDSE. After PPV, regression of inflammation was observed, although the corneal edema had progressed. The cornea evolved to decompensate due to bullous keratopathy and visual acuity of the eye decreased to no light perception after 3 months. A 87-year-old male who underwent phacoemulsification and intraocular lens implantation 2 days previously was hospitalized due to severe ocular pain and visual loss. There was severe inflammation, and the visual acuity was no light perception. The patient received only intravitreal injections of antibiotics due to severe corneal necrosis. The aqueous humor revealed SDSE. Four days after intravitreal injection, erythema and swelling of the eyelid of the affected eye was observed, and diagnosed as panophthalmitis. After treatment with intravenous antibiotics, cellulitis of the eyelid was resolved. The eye progressed as phthisis after 3 months without recurrence. Conclusions: Postoperative SDSE endophthalmitis showed aggressive and hyperacute presentation, resulting in blindness despite prompt treatment. SDSE is an emerging organism and should be considered a potential cause of postoperative endophthalmitis. KCI Citation Count: 0